Some Application for a Fuzzy Differential Equation and Solve by Runge-Kutta Method - Qasim Abd Ali Tayyeh (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2024)
In this article, the starting condition was defined using a fuzzy initial value problem (IVP). Additionally, we discussed various methods for solving fuzzy differential equations, including the modified two-step Simpson method and Runge-Kutta of orders (two, three, four, five, and six). For each method, we provided a numerical example and the known convergence rates of the solutions. Then we discussed the comparison of the solutions of all methods, using computer software to offer rough solutions for the Runge Kutta method. And take some application solve by Runge-Kutta in physics and medical